B Cell IL-4 Drives Th2 Responses In Vivo, Ameliorates Allograft Rejection, and Promotes Allergic Airway Disease - Song, Zhixing; Yuan, Wenjia; Zheng, Leting; Wang, Xingan; Kuchroo, Vijay K.; Mohib, Kanishka; Rothstein, David M. (Frontiers in Immunology, 2022)
B cells can be polarized to express various cytokines. The role of IFN and IL-10, expressed respectively by B effector 1 (Be1) and Bregs, have been established in pathogen clearance, tumor growth, autoimmunity and allograft rejection. However, the in vivo role of B cell IL-4, produced by Be2 cells, remains to be established. We developed B-IL-4/13 iKO mice carrying a tamoxifen-inducible B cell-specific deletion of IL-4 and IL-13. After alloimmunization, B-IL-4/13 iKO mice exhibited decreased IL-4+ Th2 cells and IL-10+ Bregs without impact on Th1, Tregs, or CD8 T cell responses. Moreover, B-IL-4/13 iKO mice rejected islet allografts more rapidly, even when treated with tolerogenic anti-TIM-1 mAb. In ovalbumin-induced allergic airway disease (AAD), B-IL-4/13 iKO mice had reduced inflammatory cells in BAL, and preserved lung histology with markedly decreased infiltration by IL-4+ and IL-5+ CD4+ T cells. Hence, B cell IL-4 is a major driver of Th2 responses in vivo which promotes allograft survival, and conversely, worsens AAD.